Effect of Bidirectional Hysteretic Dampers on the Seismic Performance of Skewed Multi-Span Highway Bridges - Sofía Aldea; Ramiro Bazáez; Pablo Heresi; Rodrigo Astroza (Buildings, 2024)
Bridges are one of the most critical and costly structures on road networks. Thus, their integrity and operation must be preserved to prevent safety concerns and connectivity losses after seismic events. Recent large-magnitude earthquakes have revealed a series of vulnerabilities in multi-span highway bridges. In particular, skewed bridges have been severely damaged due to their susceptibility to developing excessive in-plane deck rotations and span unseating. Although seismic design codes have been updated to prescribe larger seating lengths and have incorporated unseating prevention devices, such as shear keys and cable restrainers, research on the seismic performance of skewed bridges with passive energy-dissipation devices is still limited. Therefore, this study focuses on assessing the effectiveness of implementing hysteretic dampers on skewed bridges. With that aim, dampers with and without recentering capabilities are designed and incorporated in representative Chilean skewed bridges to assess their contribution to seismic performance. Three-dimensional nonlinear finite element models, multiple-stripe analysis, and fragility curves are utilized to achieve this objective. The results show that incorporating bidirectional dampers can effectively improve the seismic performance of skewed bridges at different hazard levels by limiting in-plane deck rotations independently of their skew angle. Additionally, the influence of external shear keys and damper hysteretic behavior is analyzed, showing that these parameters have a low influence on bridge performance when bidirectional dampers are incorporated.